back to the math tutorial index back to the math tutorial index

The Binomial Theorem

We know that \begin{eqnarray*} (x+y)^0&=&1\\ (x+y)^1&=&x+y\\ (x+y)^2&=&x^2+2xy+y^2 \end{eqnarray*} and we can easily expand \[(x+y)^3=x^3+3x^2y+3xy^2+y^3.\] For higher powers, the expansion gets very tedious by hand! Fortunately, the Binomial Theorem gives us the expansion for any positive integer power of $(x+y)$:

Binomial Theorem

For any positive integer $n$, \[(x+y)^n=\sum^n_{k=0} \left(\begin{array}{c} n\\ k \end{array}\right)x^{n-k}y^k\] where $$ \displaystyle\left(\begin{array}{c} n\\ k \end{array}\right)=\frac{(n)(n-1)(n-2)\cdots(n-(k-1))}{k!}=\frac{n!}{k!(n-k)!}. $$

Proof by Induction     Combinatorial Proof     Connection to Pascal's Triangle

Example

By the Binomial Theorem, \begin{eqnarray*} (x+y)^3&=& \sum_{k=0}^3 \left(\begin{array}{c} 3\\ k \end{array}\right)x^{3-k}y^k\\ &=& \left(\begin{array}{c} 3\\ 0 \end{array}\right)x^3+\left(\begin{array}{c} 3\\ 1 \end{array}\right)x^2y+\left(\begin{array}{c} 3\\ 2 \end{array}\right)xy^2+\left(\begin{array}{c} 3\\ 3 \end{array}\right)y^3\\ &=& x^3+3x^2y+3xy^2+y^3 \end{eqnarray*} as expected.

Extensions of the Binomial Theorem

A useful special case of the Binomial Theorem is \[(1+x)^n=\sum^n_{k=0} \left(\begin{array}{c} n\\ k \end{array}\right)x^k\] for any positive integer $n$, which is just the Taylor series for $(1+x)^n$.

This formula can be extended to all real powers $\alpha$: \[(1+x)^{\alpha}=\sum^{\infty}_{k=0} \left(\begin{array}{c} \alpha\\ k \end{array}\right)x^k\] for any real number $\alpha$, where \[\left(\begin{array}{c} \alpha\\ k \end{array}\right)=\frac{(\alpha)(\alpha -1)(\alpha -2)\cdots (\alpha -(k-1))}{k!}=\frac{\alpha !}{k!(\alpha -k)!}.\] Notice that the formula now gives an infinite series. (When $\alpha=n$ is a positive integer, all but the first $(n+1)$ terms are $0$ since after this $n-n$ ($=0$) appears in each numerator.)

This expansion is very useful for approximating $(1+x)^{\alpha}$ for $|x|\ll 1$: \[(1+x)^\alpha =1+\alpha x+ \frac{\alpha(\alpha -1)}{2!}x^2+\frac{\alpha (\alpha -1)(\alpha -2)}{3!}x^3+\cdots.\] But for $|x|\ll 1$, higher powers of $x$ get small very quickly, so $(1+x)^{\alpha}$ can be approximated to any accuracy we need by truncating the series after a finite number of terms.

Example

For $|x|\ll 1$, \begin{eqnarray*} (1+x)^{5/2}&\approx& 1+\frac{5}{2}x,\\ (1-2x)^{100}&\approx& 1-200x,\\ (1+x^2)^{-3}&\approx& 1-3x^2. \end{eqnarray*} This type of reasoning is useful in investigating what happens when a physical system is perturbed slightly, introducing a new very small term $x$.

Key Concepts

Binomial Theorem

For any positive integer $n$, $$ (x+y)^n = \sum_{k=0}^n \left(\begin{array}{c} n \\ k \end{array}\right) x^{n-k} y^k $$ where $$ \left(\begin{array}{c} n \\ k \end{array}\right) = \frac{n(n-1)(n-2)\cdots(n-k+1)}{k!} = \frac{n!}{k!(n-k)!}. $$